A Case of Ciprofloxacin-Induced QT Prolongation and Torsade de Pointes - Hedieh Keshavarz-Bahaghighat; Sheyda Najafi; Soha Namazi; Zahra Jahangard Rafsanjani (Research Center for Rational Use of Drugs (RCRUD), 2017)
Prolongation of the QT interval is a recognized adverse effect of fluoroquinolone antibiotics. This effect on ventricular repolarization can potentially lead to life-threatening arrhythmias such as Torsade de pointes. Torsade de pointes is a polymorphic form of ventricular tachycardia identified by twisting of the QRS axis around an isoelectric point. We report a case of torsade de pointes induced by ciprofloxacin treatment. The patient experienced an acquired QT interval prolongation followed by Torsade de pointes arrhythmia with ciprofloxacin administration for ileostomy closure surgery and unfortunately expired.